Guided Questions Technique Towards The Students Recount Text Writing - Mitha Silfia; Agnes Rianti; Fanny Lieyanti; Theresia Angel Tarigan; Nurmahyuni Asrul (INTERACTION: Jurnal Pendidikan Bahasa, 2022)
In this study, students in the seventh (VII) grade of Perguruan Dharma Bakti Lubuk Pakam were examined in relation to their success in creating recount texts using the guided questioning technique. Thus, students in the seventh (VII) grade made up the research population. Two classes of 24 students each, for a total of 48 pupils, were used by the writers for their research. Purposive sampling was selected as the sampling technique from two courses, each of which included 24 pupils. In this quasi-experimental study, the pre-test and post-test written assessments were used to collect data, and both groups received a distinct course of therapy. Before the post-test, the experimental group employed the guided questions methodology and the control group the traditional approach. Because the significance was less than alpha p (a), the hypothesis was accepted when it showed sig. 2-tailed (p) 0,000 (a) 0,005. The control group's score went risen from 51,46 to 63,67. From 55,46 to 70,00, the experimental group's score climbed. The variances between the experimental group's mean score (M = 70,00; SD = 16,251; t(23) = 7,174) and the control group's mean score (M = 63,67; SD = 18,087). The study's findings thus showed that the Guided Questions Technique had a bearing on students' success in making recount texts.